Conceptual Model of Computer Utilization in 21st Century Science Learning: Grounded Theory-Informed Literature Review - Lathif, Yuniar Fahmi; Prasetya, Muhammad Gibran Alif; Yasin, Ahmad Alfian Risydan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The use of computers in science education continues to be dominated by technocentric approaches that treat technology as an end in itself rather than a means of learning. This research aims to deconstruct prevailing research trends and construct a new conceptual model explaining how computers can be used effectively in 21st-century science learning. Using a Systematic Literature Review (SLR) design with the PRISMA 2020 protocol, this study selects and analyzes high-quality articles from reputable databases. Data analysis followed a Grounded Theory-Informed approach to extract recurring patterns and build theoretical propositions inductively. Three fundamental dimensions emerged to form the new conceptual model: (1) Teacher Agency and Ecosystem Readiness as determinant input variables that precede hardware availability; (2) Hybrid Pedagogy and Distributed Scaffolding as the core process mechanism that bridges physical and digital learning experiences; and (3) Methodological Adaptability as a moderator variable that adjusts instructional strategies to the complexity level of the subject matter. This study concludes that technology effectiveness is not deterministic — it depends on an adaptive pedagogical ecosystem built around teacher capacity and contextual design. These findings carry strategic implications for curriculum developers and policymakers: prioritize discipline-specific teacher professional development, and design learning environments that pair virtual simulations with real-world experiments.